Penerapan Serta Validasi Metode Spektrofotometri Inframerah Pada Penetapan Kadar Ibuprofen Dalam Sediaan Tablet - Zuhairiah Nst; Nerdy Nerdy; Rifoni Simbolon (Herbal Medicine Journal, 2020)
Ibuprofen is one of drugs, which was used in medication rematic and arthritis, The purpose of this research was used to determination ibuprofen in the tablet, which circulates in the general whether it fulfilled requirement of drug quality, or not so that it will give the therapeutic effect. The determining of ibuprofen in tablet was done by Infrared Spectrophotometry using Methanol as a solvent at wavenumber 1709,0 cm-1 and tested it validity based on parameter accuracy using standard addition method, precision, limit of detection and limit of quantitation. Based on quantitative determination of ibuprofen in generic tablet ; Ibuprofen Sampel A was 98,36% ± 0,15%. Ibuprofen Sampel B was 102,38%± 0,21% and branded name, Sampel C, D, E in succession was 97,10% ± 0,18%; 99,34% ± 0,24%; was 103,33% ± 0,19%. The result of research indicate that determining ibuprofen in the generic tablet and branded name was fullfilled requirement of the Farmakope Indonesia Edisi IV (1995), not less than 90,0% and not more than 110,0% of the labelled amount.